A hybrid extraction level layout design for block caving. Issue 1 (2nd January 2022) - Le-Feaux, Rene; Castro, Raúl; Cortez, Diego; Gómez, René; Silva, Diego
ABSTRACT: The most widely used production level layouts in block cave mines have been the El Teniente and Herringbone. However, these patterns face some challenges that can be improved, such as reducing LHD cycle times, improved pillar geometries for a better production level stability and enhancements in time and cost during construction. In that context, this work proposes a hybrid extraction level design for Block Caving, integrating productivity and geometry to achieve a balance based on experience and theory. A methodology is proposed to compare with El Teniente layout in terms of constructability, ground support, and main operational parameters. The results indicate that a hybrid layout offers advantages compared to the El Teniente layout based on the area and input variables analysed. Although further studies are recommended for industrial validation, the results obtained here show that the proposed layout is feasible and has the potential to be applied in block cave mining.